Python geospatial development : learn to build sophisticated mapping applications from scratch using Python tools for geospatial development - Westra, Erik (Packt Pub., 2013)
This is a tutorial style book that will teach usage of Python tools for GIS using simple practical examples and then show you how to build a complete mapping application from scratch. The book assumes basic knowledge of Python. No knowledge of Open Source GIS is required. Experienced Python developers who want to learn about geospatial concepts, work with geospatial data, solve spatial problems, and build mapbased applications. This book will be useful those who want to get up to speed with Open Source GIS in order to build GIS applications or integrate GeoSpatial features into their existing application.